Promoting transformative learning through English as a lingua franca: An empirical study. - Nicos Sifakis; Stefania Kordia (Fergal Finnegan, Ted Fleming & Alexis Kokkos (Eds.), Transformative Learning in Europe: Perspectives and Practices., 2019)
This chapter provides a state-of-the-art discussion of the ways in which transformative learning could be fostered in teacher education. It focuses on programmes which aim at raising English language teachers’ awareness of the implications of the current role of English as a lingua franca (ELF), namely as an international contact language. After presenting the challenges which the ELF phenomenon poses nowadays, the transformative model for ELF-aware teacher education put forward by Sifakis is discussed, with reference to its relevance for Mezirow’s transformation theory. The transformative experiences of Kordia during her participation in an ELF-aware teacher education programme are afterwards presented, illustrating the phases of transformation she went through in her attempt to integrate ELF in her teaching practices.